Microbiologia básica de Leptospira spp.: uma ferramenta para melhorar estudos sobre leptospirose - Barbosa, L. N.; Grassmann, A. A.; Alba, V. S.; Rosa, G. A.; Rosa, E. E. B.; Mcbride, A. J. A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Introduction: Leptospirosis is a zoonosis with a high incidence worldwide, caused by spirochetes belonging to the genus Leptospira. The maintenance of the strains and the in vitro growth of the microorganism remain time-consuming and difficult to be performed. Demonstrating the need to optimize laboratory culture techniques, towards improving studies in leptospirosis.